12(12m-14y)=12(94)

Simplify each term.

Combine 12 and m.

12(m2-14y)=12(94)

Combine y and 14.

12(m2-y4)=12(94)

12(m2-y4)=12(94)

Apply the distributive property.

12m2+12(-y4)=12(94)

Cancel the common factor of 2.

Factor 2 out of 12.

2(6)m2+12(-y4)=12(94)

Cancel the common factor.

2⋅6m2+12(-y4)=12(94)

Rewrite the expression.

6m+12(-y4)=12(94)

6m+12(-y4)=12(94)

Cancel the common factor of 4.

Move the leading negative in -y4 into the numerator.

6m+12-y4=12(94)

Factor 4 out of 12.

6m+4(3)-y4=12(94)

Cancel the common factor.

6m+4⋅3-y4=12(94)

Rewrite the expression.

6m+3(-y)=12(94)

6m+3(-y)=12(94)

Multiply -1 by 3.

6m-3y=12(94)

Cancel the common factor of 4.

Factor 4 out of 12.

6m-3y=4(3)94

Cancel the common factor.

6m-3y=4⋅394

Rewrite the expression.

6m-3y=3⋅9

6m-3y=3⋅9

Multiply 3 by 9.

6m-3y=27

6m-3y=27

Divide each term in 6m-3y=27 by 12.

6m-3y12=2712

Cancel the common factor of 6m-3y and 12.

Factor 3 out of 6m.

3(2m)-3y12=2712

Factor 3 out of -3y.

3(2m)+3(-y)12=2712

Factor 3 out of 3(2m)+3(-y).

3(2m-y)12=2712

Cancel the common factors.

Factor 3 out of 12.

3(2m-y)3(4)=2712

Cancel the common factor.

3(2m-y)3⋅4=2712

Rewrite the expression.

2m-y4=2712

2m-y4=2712

2m-y4=2712

Cancel the common factor of 27 and 12.

Factor 3 out of 27.

2m-y4=3(9)12

Cancel the common factors.

Factor 3 out of 12.

2m-y4=3⋅93⋅4

Cancel the common factor.

2m-y4=3⋅93⋅4

Rewrite the expression.

2m-y4=94

2m-y4=94

2m-y4=94

2m-y4=94

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

2m-y=9

Add y to both sides of the equation.

2m=9+y

Divide each term in 2m=9+y by 2.

2m2=92+y2

Cancel the common factor of 2.

Cancel the common factor.

2m2=92+y2

Divide m by 1.

m=92+y2

m=92+y2

m=92+y2

Solve for m 12(1/2m-1/4y)=12(9/4)